2011
DOI: 10.1016/j.jamcollsurg.2010.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Caprini Risk Assessment Model in Plastic and Reconstructive Surgery Patients

Abstract: Background The VTEPS Network is a consortium of five tertiary referral centers established to examine venous thromboembolism in plastic surgery patients. We report our mid-term analyses of the study’s control group to 1) evaluate the incidence of VTE in patients who receive no chemoprophylaxis and 2) validate the Caprini Risk Assessment Model (RAM) in plastic surgery patients. Study Design Medical record review was performed at VTEPS centers for all eligible plastic surgery patients between March 2006 and Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
236
2
16

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 364 publications
(262 citation statements)
references
References 49 publications
8
236
2
16
Order By: Relevance
“…This study was conducted from June to September 2015. Based on the literature which proves the validity of Caprini risk assessment model, this model was used to evaluate patients' risk scores to define risk category (10).…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted from June to September 2015. Based on the literature which proves the validity of Caprini risk assessment model, this model was used to evaluate patients' risk scores to define risk category (10).…”
Section: Methodsmentioning
confidence: 99%
“…Pannucci et al utilized the National Burn Repository (NBR) database to retrospectively assess all VTE events in this patient population to formulate a VTE risk score. The score was generated by taking into account both the size of the burn and the presence of inhalational injury [7,11]. The matched case-control retrospective study also assessed acquired inpatient risk factors and concluded that the number of operations, pneumonia and the use of central venous catheters were directly related to the development of VTE [7,11].…”
Section: Discussionmentioning
confidence: 99%
“…The Caprini assessment tool has been clinically evaluated and supported by ASPS [7]. It has also been modified for specific use in patients undergoing plastic surgery and validated in a recent study [8]. …”
Section: Discussionmentioning
confidence: 99%